2017
DOI: 10.3389/fncel.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Accumulation of β-Sheet-Rich Proteins in Offspring Brain following Maternal Exposure to Carbon Black Nanoparticles

Abstract: Environmental stimulation during brain development is an important risk factor for the development of neurodegenerative disease. Clinical evidence indicates that prenatal exposure to particulate air pollutants leads to diffuse damage to the neurovascular unit in the developing brain and accelerates neurodegeneration. Maternal exposure to carbon black nanoparticles (CB-NPs), used as a model for particulate air pollution, induces long-lasting diffuse perivascular abnormalities. We aimed to comprehensively charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“… 37 Thus, it is commonly used for the secondary structure analysis 38 that can also be applied to in situ analyses under microscopy. 39 Not only the secondary structure but also the aggregation of the Aβ peptide in solvents can be analyzed using FT-IR spectroscopy. 40 Hydrochloric acid (1 mmol/L) was used to maintain the dispersibility of the CeF 3 NPs.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Thus, it is commonly used for the secondary structure analysis 38 that can also be applied to in situ analyses under microscopy. 39 Not only the secondary structure but also the aggregation of the Aβ peptide in solvents can be analyzed using FT-IR spectroscopy. 40 Hydrochloric acid (1 mmol/L) was used to maintain the dispersibility of the CeF 3 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of PM on ER stress may contribute to the abnormal deposition of Aβ and α-synuclein in the brains of children from MCMA, leading to the susceptibility of late-life AD and onset of PD [ 15 ]. By using in situ Fourier transform infrared microspectroscopy to study the conformation of the proteins in the brain, proteins with β-sheet structure, a form of misfolded protein that are commonly seen in neurodegenerative diseases such as AD, accumulate in the perivascular space in the brains of the offsprings that were maternally exposed to carbon black nanoparticles [ 109 ]. These misfolded proteins may be in the process of clearance from the brain [ 109 ], which may activate the microglia and astrocytes.…”
Section: Pm May Induce Neurotoxicity Oxidative Stress Neuroinflammati...mentioning
confidence: 99%
“…By using in situ Fourier transform infrared microspectroscopy to study the conformation of the proteins in the brain, proteins with β-sheet structure, a form of misfolded protein that are commonly seen in neurodegenerative diseases such as AD, accumulate in the perivascular space in the brains of the offsprings that were maternally exposed to carbon black nanoparticles [ 109 ]. These misfolded proteins may be in the process of clearance from the brain [ 109 ], which may activate the microglia and astrocytes. Further analysis showed that perivascular macrophages and astrocytes were activated and showed ER stress in the offsprings’ brains when they were maternally exposed to carbon black nanoparticle [ 110 ].…”
Section: Pm May Induce Neurotoxicity Oxidative Stress Neuroinflammati...mentioning
confidence: 99%
“…The problem of NPs crossing the placental barrier at the early stages of fetal development, and the documentation of neurons and primitive glia displaying nuclear, organelle, and cytoplasmic Fe, Ti, and Al alloys, Hg, Cu, Ca, Sn, and Si NPs is a serious medical concern ( 15 ). Documentation of NPs in experimental animals shows maternal exposures resulting in severe offspring alterations in neurogenesis and synaptogenesis, perivascular accumulation of β sheet rich proteins, and perivascular ER stress with the accumulation of misfolded proteins in the developing brain ( 39 41 ).…”
Section: Solid Highly Reactive Metal and Non-metal Nanoparticles Reac...mentioning
confidence: 99%